Development of a fluorescence correlation spectroscopy instrument and its application in sizing quantum dot nanoparticles - Bao, Nguyen Thi Thanh; Trung, Dinh Van (Communications in Physics, 2015)
Fluorescence correlation spectroscopy is a relatively new technique to measure and quantify the statistical fluctuations of the fluorescence signal from the measurement volume. Combining with sensitive detection method and confocal microscopy, the FCS technique has become a powerful tool in studying the dynamic properties of nanoparticles at single particle level. In this paper we present the construction of a highly sensitive FCS instrument and the measurement results from a sample of semiconductor quantum dots. We provide the analysis procedure for determining the hydrodynamic radius of the quantum dots and compare the results with that obtained directly from electron microscope imaging. The good agreement indicates the reliability of the FCS technique and open the way for further applications of this technique in studying nanoparticles.